GOOS Essential Ocean Variables: the backbone of a sustained and evolving global ocean observing system - Belén Martín Míguez; Emma Heslop; Narissa Bax; Lisandro Benedetti-Cecchi; Gabrielle Canonico; Kim Currie; Karen Evans; Albert S. Fischer; Véronique Garçon; Maria Hood; Johannes Karstensen; Ana Lara-López; et al. (Frontiers in Marine Science, 2026)
The need for ocean information has never been greater. From climate change to food security and extreme events, we need to understand the role of the ocean and better predict change and impact. This is only possible with the sustained collection of a key set of ocean observations. The Global Ocean Observing System (GOOS) coordinates international efforts to collect these Essential Ocean Variables (EOVs), which span physics, biogeochemistry, biology and ecosystem realms. Guided by three expert panels, these EOVs are used to define the needs and design of a sustained, fit for purpose global ocean observing system, aimed at maximizing investments in observing infrastructure. As the GOOS EOVs are increasingly used, it has become important to discuss and refine the understanding of this framework, to ensure that the right balance is struck between their essential nature and the need to expand to new domains and integrate with key global policies. In this paper we provide a description of the EOV framework, discuss some of the challenges in implementing it, and identify a set of recommendations for GOOS and the ocean observing community to take forward. These recommendations include increasing the transparency of the EOV adoption process, and the need to periodically assess the EOVs in consultation with observing communities and with the entities managing other global essential variable frameworks in cross cutting realms such as climate and biodiversity. This will contribute to building a useful and responsive global ocean observing system that delivers the observations required to meet societal needs.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Relating social, ecological, and technological vulnerability to future flood exposure at two spatial scales in four U.S. cities - Jason Sauer; Arun Pallathadka; Idowu Ajibade; Marta Berbés-Blázquez; Heejun Chang; Elizabeth M. Cook; Nancy B. Grimm; David M. Iwaniec; Robert Lloyd; Gregory C. Post (Sustainable Cities and Society, 2023)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Considering the Influence of Coronary Motion on Artery-Specific Biomechanics Using Fluid–Structure Interaction Simulation - Nicholas A. T. Fogell; Miten Patel; Pan Yang; Roosje M. Ruis; David B. Garcia; Jarka Naser; Fotios Savvopoulos; Clint Davies Taylor; Anouk L. Post; Ryan M. Pedrigi; Ranil de Silva; Rob Krams (Annals of Biomedical Engineering, 2023)
The endothelium in the coronary arteries is subject to wall shear stress and vessel wall strain, which influences the biology of the arterial wall. This study presents vessel-specific fluid–structure interaction (FSI) models of three coronary arteries, using directly measured experimental geometries and boundary conditions. FSI models are used to provide a more physiologically complete representation of vessel biomechanics, and have been extended to include coronary bending to investigate its effect on shear and strain. FSI both without- and with-bending resulted in significant changes in all computed shear stress metrics compared to CFD ( p = 0.0001). Inclusion of bending within the FSI model produced highly significant changes in Time Averaged Wall Shear Stress (TAWSS) + 9.8% LAD, + 8.8% LCx, − 2.0% RCA; Oscillatory Shear Index (OSI) + 208% LAD, 0% LCx, + 2600% RCA; and transverse wall Shear Stress (tSS) + 180% LAD, + 150% LCx and + 200% RCA (all p

Alternative Biogeochemical States of River Pools Mediated by Hippo Use and Flow Variability - Christopher L. Dutton; Amanda L. Subalusky; Stephen K. Hamilton; Ella C. Bayer; Laban Njoroge; Emma J. Rosi; David M. Post (Ecosystems, 2021)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Organic matter and nutrient inputs from large wildlife influence ecosystem function in the Mara River, Africa - Amanda L. Subalusky; Christopher L. Dutton; Laban Njoroge; Emma J. Rosi; David M. Post (Ecology, 2018)
Animals can be important vectors for the movement of resources across ecosystem boundaries. Animals add resources to ecosystems primarily through egestion, excretion, and carcasses, and the stoichiometry and bioavailability of these inputs likely interact with characteristics of the recipient ecosystem to determine their effects on ecosystem function. We studied the influence of hippopotamus excretion/egestion and wildebeest carcasses, and their interactions with discharge, in the Mara River, Kenya. We measured nutrient dissolution and decomposition rates of wildlife inputs, the influence of inputs on nutrient concentrations and nutrient limitation in the river and the influence of inputs on biofilm growth and function in both experimental streams and along a gradient of inputs in the river. We found that hippopotamus excretion/egestion increases ammonium and coarse particulate organic matter in the river, and wildebeest carcasses increase ammonium, soluble reactive phosphorus, and total phosphorus. Concentrations of dissolved carbon and nutrients in the water column increased along a gradient of wildlife inputs and during low discharge, although concentrations of particulate carbon decreased during low discharge due to deposition on the river bottom. Autotrophs were nitrogen limited and heterotrophs were carbon limited and nitrogen and phosphorus colimited upstream of animal inputs but there was no nutrient limitation downstream of inputs. In experimental streams, hippo and wildebeest inputs together increased biofilm gross primary production ( GPP) and respiration ( R ). These results differed in the river, where low concentrations of hippo inputs increased gross primary production ( GPP ) and respiration ( R ) of biofilms, but high concentrations of hippo inputs in conjunction with wildebeest inputs decreased GPP . Our research shows that inputs from large wildlife alleviate nutrient limitation and stimulate ecosystem metabolism in the Mara River and that the extent to which these inputs subsidize the ecosystem is mediated by the quantity and quality of inputs and discharge of the river ecosystem. Thus, animal inputs provide an important ecological subsidy to this river, and animal inputs were likely important in many other rivers prior to the widespread extirpation of large wildlife.

Publisher Correction to: Background invertebrate herbivory on dwarf birch (Betula glandulosa-nana complex) increases with temperature and precipitation across the tundra biome - Isabel C. Barrio; Elin Lindén; Mariska Te Beest; Johan Olofsson; Adrian Rocha; Eeva M. Soininen; Juha M. Alatalo; Tommi Andersson; Ashley Asmus; Julia Boike; Kari Anne Bråthen; John P. Bryant; et al. (Polar Biology, 2018)

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Life history traits and functional processes generate multiple pathways to ecological stability - John P. DeLong; Torrance C. Hanley; Jean P. Gibert; Linda M. Puth; David M. Post (Ecology, 2018)
Stability contributes to the persistence of ecological communities, yet the interactions among different stabilizing forces are poorly understood. We assembled mesocosms with an algal resource and one to eight different clones of the consumer Daphnia ambigua and tracked algal and Daphnia abundances through time. We then fitted coupled ordinary differential equations ( ODE s) to the consumer–resource time series. We show that variation in different components of stability (local stability and the magnitude of population fluctuations) across mesocosms arises through variation in life history traits and the functional processes represented by ODE model parameters. Local stability was enhanced by increased algal growth rate and Daphnia mortality and foraging rate. Population fluctuations were dampened by high Daphnia conversion efficiency and lower interaction strengths, low algal growth rate, high Daphnia death rate, and low Daphnia foraging. These results indicate that (1) stability in consumer–resource systems may arise through the net effect of multiple related stabilizing pathways and (2) different aspects of stability can vary independently and may respond in opposite directions to the same forces.

Background invertebrate herbivory on dwarf birch (Betula glandulosa-nana complex) increases with temperature and precipitation across the tundra biome - Isabel C. Barrio; Elin Lindén; Mariska Te Beest; Johan Olofsson; Adrian Rocha; Eeva M. Soininen; Juha M. Alatalo; Tommi Andersson; Ashley Asmus; Julia Boike; Kari Anne Bråthen; John P. Bryant; et al. (Polar Biology, 2017)

Genetic associations with lipoprotein subfraction measures differ by ethnicity in the multi-ethnic study of atherosclerosis (MESA) - Zhe Wang; Ani Manichukal; David C. Goff; Samia Mora; Jose M. Ordovas; Nicholas M. Pajewski; Wendy S. Post; Jerome I. Rotter; Michele M. Sale; Stephanie A. Santorico; David Siscovick; Michael Y. Tsai; et al. (Human Genetics, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Reconciling the role of terrestrial leaves in pond food webs: a whole‐ecosystem experiment - Meredith A. Holgerson; David M. Post; David K. Skelly (Ecology, 2016)
Terrestrial carbon and nutrients can subsidize the detrital pool of freshwater ecosystems; yet, the importance of terrestrial subsidies to lake and pond food webs is uncertain and debated. Terrestrial detritus is expected to have the greatest impact on food webs when water bodies are small and shallow with low levels of incident light. Temporary forested ponds fit this description and are often assumed to have a leaf detritus‐based food web, but this has not been quantified. In a whole‐ecosystem experiment, we traced the flow of isotopically enriched leaf litter to primary producers and consumers in a small, forested pond. We found that terrestrial leaves provided nutrients to algae, offering an indirect pathway in which leaf litter can enter the food web. Terrestrial leaves were also consumed directly, and larval caddisfly ( Limnephilus sp.) shredders likely mobilized leaf nutrients to other consumers, a process overlooked in many previous small‐scale experiments that did not incorporate shredders. Unexpectedly, most consumers relied heavily upon algal food pathways despite low light and net heterotrophic conditions. Overall, our study highlights the interconnectedness of algal and leaf litter pathways in small pond food webs, and emphasizes that algal pathways are prevalent and important even in small, shaded ponds with high loads of terrestrial leaf litter.

Deer feeding selectivity for invasive plants - Kristine M. Averill; David A. Mortensen; Erica A. H. Smithwick; Eric Post (Biological Invasions, 2016)

Phytoplankton composition modifies predator-driven life history evolution in Daphnia - Matthew R. Walsh; Kimberly J. La Pierre; David M. Post (Evolutionary Ecology, 2014)

Ammonium cycling in the rocky intertidal: Remineralization, removal, and retention - Santhiska Pather; Catherine A. Pfister; David M. Post; Mark A. Altabet (Limnology and Oceanography, 2014)
Rocky intertidal productivity is traditionally thought to be sustained almost solely by upwelled nitrate with remineralized forms of minor importance. Using tidepools as natural experimental mesocosms, we conducted 15 N‐tracer experiments to test whether ammonium remineralized within the rocky intertidal is also a significant source of fixed N to localized ecosystem production. Comparison of tidepools with and without the dominant bivalve Mytilus californianus allowed consideration of its role in NH + 4 cycling. Closed water‐incubation bottles were used to investigate the contribution of suspended microbes to NH + 4 cycling. Tidepools with mussels had both greater NH + 4 remineralization (two times) and NH + 4 removal as compared with those without, with daytime rates greater than nighttime rates. Incorporation of NH + 4 tracer by particulate organic matter and macroalgae, and the persistence of this signal in tidepools for several days following the experiment, showed retention of autochthonous NH + 4 in the system. Remineralization rates were tightly correlated to removal rates when compared over all treatments and experiments, but NH + 4 remineralization was significantly greater than removal, suggesting a surplus available to nearshore primary producers.

Recent parallel divergence in body shape and diet source of alewife life history forms - Andrew W. Jones; Eric P. Palkovacs; David M. Post (Evolutionary Ecology, 2013)

Historical changes in nutrient inputs from humans and anadromous fishes in New England's coastal watersheds - Cornelia W. Twining; Derek C. West; David M. Post (Limnology and Oceanography, 2013)
Prior to Euro‐American contact, anadromous alewives ( Alosa pseudoharengus ) were abundant throughout eastern North America. In the 400 yr since Euro‐American settlement began in the region, anadromous alewife populations have declined by an order of magnitude or more while human land use has simultaneously intensified. Here we asked how lake nutrient inputs in the southern New England region have changed over the past 400 yr by examining nutrient inputs to four lakes in coastal Connecticut that differ in their land‐use history and their history of accessibility to anadromous alewife. We estimated the flux of nitrogen and phosphorus from both anadromous alewife and the landscape and conducted a paleoecological analysis of stable isotopes ( δ 15 N, total δ 13 C, organic δ 13 C) and nutrients (N : P, C : N, organic C) from lake sediment cores in each of our study watersheds. Nutrient loading models suggest that allochthonous nutrient inputs are now dominated by watershed land use and our paleoecological data also reflect major changes in human land use. Loading models also suggest that prior to Euro‐American contact, anadromous alewife runs historically provided up to 95% of allochthonous phosphorus inputs and up to 68% of allochthonous nitrogen inputs to the region's coastal lakes. However, paleoecological data suggest that even the large nutrient inputs from abundant past alewife populations may never have had the same long‐term effect on lake nutrient dynamics as those from the landscape due to the unique combination of the alewife's life history and coastal Connecticut's climate and geomorphology.

Genetic variants associated with VLDL, LDL and HDL particle size differ with race/ethnicity - Alexis C. Frazier-Wood; Ani Manichaikul; Stella Aslibekyan; Ingrid B. Borecki; David C. Goff; Paul N. Hopkins; Chao-Qiang Lai; Jose M. Ordovas; Wendy S. Post; Stephen S. Rich; Michèle M. Sale; David Siscovick; et al. (Human Genetics, 2013)

Reversible severe encephalitis and word deafness following rapid immune reconstitution in AIDS: a case report - David Roh; Melanie D. Glenn; Carol K. Petito; M. Judith Donovan Post; Ashok Verma (Journal of NeuroVirology, 2013)

Global assessment of experimental climate warming on tundra vegetation: heterogeneity over space and time - Sarah C. Elmendorf; Gregory H. R. Henry; Robert D. Hollister; Robert G. Björk; Anne D. Bjorkman; Terry V. Callaghan; Laura Siegwart Collier; Elisabeth J. Cooper; Johannes H. C. Cornelissen; Thomas A. Day; Anna Maria Fosaa; William A. Gould; et al. (Ecology Letters, 2012)
Ecology Letters (2011) Abstract Understanding the sensitivity of tundra vegetation to climate warming is critical to forecasting future biodiversity and vegetation feedbacks to climate. In situ warming experiments accelerate climate change on a small scale to forecast responses of local plant communities. Limitations of this approach include the apparent site‐specificity of results and uncertainty about the power of short‐term studies to anticipate longer term change. We address these issues with a synthesis of 61 experimental warming studies, of up to 20 years duration, in tundra sites worldwide. The response of plant groups to warming often differed with ambient summer temperature, soil moisture and experimental duration. Shrubs increased with warming only where ambient temperature was high, whereas graminoids increased primarily in the coldest study sites. Linear increases in effect size over time were frequently observed. There was little indication of saturating or accelerating effects, as would be predicted if negative or positive vegetation feedbacks were common. These results indicate that tundra vegetation exhibits strong regional variation in response to warming, and that in vulnerable regions, cumulative effects of long‐term warming on tundra vegetation – and associated ecosystem consequences – have the potential to be much greater than we have observed to date.

Microbial rhodopsins on leaf surfaces of terrestrial plants - Nof Atamna‐Ismaeel; Omri M. Finkel; Fabian Glaser; Itai Sharon; Ron Schneider; Anton F. Post; John L. Spudich; Christian von Mering; Julia A. Vorholt; David Iluz; Oded Béjà; Shimshon Belkin (Environmental Microbiology, 2012)
Summary The above‐ground surfaces of terrestrial plants, the phyllosphere, comprise the main interface between the terrestrial biosphere and solar radiation. It is estimated to host up to 10 26 microbial cells that may intercept part of the photon flux impinging on the leaves. Based on 454‐pyrosequencing‐generated metagenome data, we report on the existence of diverse microbial rhodopsins in five distinct phyllospheres from tamarisk ( Tamarix nilotica ), soybean ( Glycine max ), Arabidopsis ( Arabidopsis thaliana ), clover ( Trifolium repens ) and rice ( Oryza sativa ). Our findings, for the first time describing microbial rhodopsins from non‐aquatic habitats, point towards the potential coexistence of microbial rhodopsin‐based phototrophy and plant chlorophyll‐based photosynthesis, with the different pigments absorbing non‐overlapping fractions of the light spectrum.

Experimental evidence that phenotypic divergence in predators drives community divergence in prey - Eric P. Palkovacs; David M. Post (Ecology, 2009)
Studies of adaptive divergence have traditionally focused on the ecological causes of trait diversification, while the ecological consequences of phenotypic divergence remain relatively unexplored. Divergence in predator foraging traits, in particular, has the potential to impact the structure and dynamics of ecological communities. To examine the effects of predator trait divergence on prey communities, we exposed zooplankton communities in lake mesocosms to predation from either anadromous or landlocked (freshwater resident) alewives, which have undergone recent and rapid phenotypic differentiation in foraging traits (gape width, gill raker spacing, and prey size‐selectivity). Anadromous alewives, which exploit large prey items, significantly reduced the mean body size, total biomass, species richness, and diversity of crustacean zooplankton relative to landlocked alewives, which exploit smaller prey. The zooplankton responses observed in this experiment are consistent with patterns observed in lakes. This study provides direct evidence that phenotypic divergence in predators, even in its early stages, can play a critical role in determining prey community structure.

AN EXPERIMENTAL DISTURBANCE ALTERS FISH SIZE STRUCTURE BUT NOT FOOD CHAIN LENGTH IN STREAMS - Annika W. Walters; David M. Post (Ecology, 2008)
Streams experience frequent natural disturbance and are undergoing considerable anthropogenic disturbance due to dam construction and water diversion. Disturbance is known to impact community structure, but its effect on food chain length is still a matter of considerable debate. Theoretical models show that longer food chains are less resilient to disturbance, so food chain length is predicted to be shorter following a disturbance event. Here we experimentally test the effect of disturbance on food chain length in streams by diverting stream flow. We found that our experimental low‐flow disturbance did not alter food chain length. We did see an effect on body‐size structure in our food webs suggesting that food chain length may be an insensitive indicator of disturbance. We suggest that habitat heterogeneity and food web complexity buffer the effect of disturbance on food chain length. The theoretical predictions of disturbance on food chain length are only likely to be seen in homogeneous systems that closely approximate the linear food chains the models are based upon.

ECOSYSTEM SIZE, BUT NOT DISTURBANCE, DETERMINES FOOD‐CHAIN LENGTH ON ISLANDS OF THE BAHAMAS - Gaku Takimoto; David A. Spiller; David M. Post (Ecology, 2008)
Ecologists have long struggled to explain variation in food‐chain length among natural ecosystems. Food‐chain length is predicted to be shorter in ecosystems subjected to greater disturbance because longer chains are theoretically less resilient to perturbation. Moreover, food‐chain length is expected to be longer in larger ecosystems because increasing ecosystem size increases species richness and stabilizes predator–prey interactions, or increases total resource availability. Here we test the roles of disturbance and ecosystem size in determining the food‐chain length of terrestrial food webs on Bahamian islands. We found that disturbance affected the identity of top predators, but did not change food‐chain length because alternative top predators occupied similar trophic positions. On the other hand, a 10 6 ‐fold increase in ecosystem size elevated food‐chain length by one trophic level. We suggest that the effect of disturbance on food‐chain length is weak when alternate top predators are trophic omnivores and have similar trophic positions. This and previous work in lakes suggest that ecosystem size may be a strong determinant of food‐chain length in both aquatic and terrestrial ecosystems.

Marine resource flows to terrestrial arthropod predators on a temperate island: the role of subsidies between systems of similar productivity - Achim Paetzold; Michelle Lee; David M. Post (Oecologia, 2008)

Independent evolutionary origins of landlocked alewife populations and rapid parallel evolution of phenotypic traits - ERIC P. PALKOVACS; KIRSTIN B. DION; DAVID M. POST; ADALGISA CACCONE (Molecular Ecology, 2008)
Alewife, Alosa pseudoharengus , populations occur in two discrete life‐history variants, an anadromous form and a landlocked (freshwater resident) form. Landlocked populations display a consistent pattern of life‐history divergence from anadromous populations, including earlier age at maturity, smaller adult body size, and reduced fecundity. In Connecticut (USA), dams constructed on coastal streams separate anadromous spawning runs from lake‐resident landlocked populations. Here, we used sequence data from the mtDNA control region and allele frequency data from five microsatellite loci to ask whether coastal Connecticut landlocked alewife populations are independently evolved from anadromous populations or whether they share a common freshwater ancestor. We then used microsatellite data to estimate the timing of the divergence between anadromous and landlocked populations. Finally, we examined anadromous and landlocked populations for divergence in foraging morphology and used divergence time estimates to calculate the rate of evolution for foraging traits. Our results indicate that landlocked populations have evolved multiple times independently. Tests of population divergence and estimates of gene flow show that landlocked populations are genetically isolated, whereas anadromous populations exchange genes. These results support a ‘phylogenetic raceme’ model of landlocked alewife divergence, with anadromous populations forming an ancestral core from which landlocked populations independently diverged. Divergence time estimates suggest that landlocked populations diverged from a common anadromous ancestor no longer than 5000 years ago and perhaps as recently as 300 years ago, depending on the microsatellite mutation rate assumed. Examination of foraging traits reveals landlocked populations to have significantly narrower gapes and smaller gill raker spacings than anadromous populations, suggesting that they are adapted to foraging on smaller prey items. Estimates of evolutionary rates (in haldanes) indicate rapid evolution of foraging traits, possibly in response to changes in available resources.

Testing the productive-space hypothesis: rational and power - David M. Post (Oecologia, 2007)

Getting to the fat of the matter: models, methods and assumptions for dealing with lipids in stable isotope analyses - David M. Post; Craig A. Layman; D. Albrey Arrington; Gaku Takimoto; John Quattrochi; Carman G. Montaña (Oecologia, 2007)

Studying invasion: have we missed the boat? - Linda M. Puth; David M. Post (Ecology Letters, 2005)
Invasive species, and the ensuing homogenization of the world's biota, form a global problem with consequences ranging from the decline and extirpation of native species to threats to human health. The magnitude of this issue demands a thorough understanding of the invasion process, which consists of three main stages: initial dispersal, establishment of self‐sustaining populations, and spread. To assess the relative distribution of research effort among these stages, we conducted a literature review using 873 articles published in 23 major journals over the past 10 years. Of the 873 papers, only 96 (11.0%) studied initial dispersal, and only half of these (6.2% of the total) were empirical. As the first stage in a contingent process, we argue that initial dispersal is the best stage during which to direct management efforts. In addition, initial dispersal has direct relevance for fundamental ecological questions regarding community assembly and metacommunity dynamics. In so far that answering these questions and preventing invasion are goals of ecologists, the disparity in research effort noted here suggests that ecologists need to expand their efforts to include more research on initial dispersal.

Detritus, trophic dynamics and biodiversity - John C. Moore; Eric L. Berlow; David C. Coleman; Peter C. de Ruiter; Quan Dong; Alan Hastings; Nancy Collins Johnson; Kevin S. McCann; Kim Melville; Peter J. Morin; Knute Nadelhoffer; Amy D. Rosemond; et al. (Ecology Letters, 2004)
Traditional approaches to the study of food webs emphasize the transfer of local primary productivity in the form of living plant organic matter across trophic levels. However, dead organic matter, or detritus, a common feature of most ecosystems plays a frequently overlooked role as a dynamic heterogeneous resource and habitat for many species. We develop an integrative framework for understanding the impact of detritus that emphasizes the ontogeny and heterogeneity of detritus and the various ways that explicit inclusion of detrital dynamics alters generalizations about the structure and functioning of food webs. Through its influences on food web composition and dynamics, detritus often increases system stability and persistence, having substantial effects on trophic structure and biodiversity. Inclusion of detrital heterogeneity in models of food web dynamics is an essential new direction for ecological research.

Molecular diversity among marine picophytoplankton as revealed by psbA analyses - Gil Zeidner; Christina M. Preston; Edward F. Delong; Ramon Massana; Anton F. Post; David J. Scanlan; Oded Béjà (Environmental Microbiology, 2003)
Summary Photosynthetic microorganisms play a crucial role in the marine environment. In vast areas of the oceans, marine primary productivity is performed by cells smaller than 2–3 µm (picoplankton). Here, we report on molecular analyses of the conserved photosynthetic psbA gene (coding for protein D1 of photosystem II reaction centre) as a diversity indicator of naturally occurring marine oxygenic picophytoplankton. The psbA genes proved to be good indicators of the presence of a wide variety of photosynthetic marine microbial groups, including new cyanobacterial groups and eukaryotic algae (prasinophytes). Furthermore, using environmental bacterial artificial chromosome (BAC) libraries, we were able to correlate psbA genes with small subunit rRNAs and, therefore, to confirm their phylogenetic affiliation.

SINGLE-NUCLEOTIDE POLYMORPHISM OF THE UROKINASE-PLASMINOGEN ACTIVATOR GENE DURING AGING AND TRANSFORMATION OF HUMAN DIPLOID KIDNEY CELL CULTURES - SAFEDIN H. BEQAJ; DAVID POST; JON M. RYAN (In Vitro Cellular & Developmental Biology - Animal, 2003)

Nutrient cycling at the landscape scale: The role of diel foraging migrations by geese at the Bosque del Apache National Wildlife Refuge, New Mexico - James F. Kitchell; Daniel E. Schindler; Brian R. Herwig; David M. Post; Mark H. Olson; Michael Oldham (Limnology and Oceanography, 1999)
Wildlife refuges are sites of dense aggregations of wintering waterfowl. Refuge managers are concerned about local water‐quality effects and the amount of birdborne nutrient load that might cause eutrophication in roosting ponds and(or) be exported to downstream systems. We initiated this research effort to test the hypothesis that daily feeding migrations by geese represented a significant source of nutrients to wetland systems at the Bosque del Apache National Wildlife Refuge in the middle Rio Grande River valley of New Mexico. We documented the role of geese in translocating nutrients through a combination of time budget and mass balance models for birds, bioassays of phytoplankton growth, and stable isotope methods that trace the source of nitrogen to food webs. Geese increased the nutrient loading rates in some wetland ponds by up to 40% for total nitrogen and 75% for total phosphorus. Bioassays revealed that nitrogen was consistently limiting to primary production by algae in the ponds. Chlorophyll levels increased in proportion to bird densities. Fish and crayfish from the ponds intensively used by birds had very low stable nitrogen signatures relative to those from the Rio Grande River. This result derived from the low 15 N in alfalfa and corn, which were the primary forage for birds, and accumulated through food webs in proportion to bird use of individual ponds as roosting areas. In general, the wetland ponds functioned efficiently in retaining the birdborne, allochthonous nutrient load and only modest amounts of the total nitrogen or phosphorus were exported downstream.

Seasonal effects of variable recruitment of a dominant piscivore on pelagic food web structure - David M. Post; Stephen R. Carpenter; David L. Christensen; Kathryn L. Cottingham; James F. Kitchell; Daniel E. Schindler; James R. Hodgson (Limnology and Oceanography, 1997)
Piscivorous fish play an important role in regulating lake food web structure. However, most ultimately piscivorous fish pass through a period of planktivory before becoming piscivorous. In 1993 and 1994, two large cohorts of young‐of‐the‐year largemouth bass ( Micropterus salmoides ) were recorded in Paul Lake, Michigan. The 1993 and 1994 cohorts were the largest recorded in data extending back to 1984 and occurred during a period in which adult and juvenile bass biomass was low. In 1993, consumption of large‐bodied zooplankton by the young‐of‐the‐year cohort eliminated large‐bodied cladocerans by the middle of August. As large cladocerans declined, small cladocerans, especially Bosmina longirostris , increased. By early September the biomass of B. longirostris was similar to that of the entire cladoceran community in previous years. Coincident with the shifts in the cladoceran community were increases in epilimnetic Chl a concentrations µ m. However, total epilimnetic Chl a did not increase. In contrast, the 1994 cohort had no discernible effect on pelagic food web structure because production of large‐bodied zooplankton rapidly exceeded predation. Our results show the potential for large cohorts of piscivorous fish to affect food web structure, at a seasonal scale, through intense planktivory.